Intertextuality and pastiche: the perfect recipe, or bland mediocrity? The EU copyright exception of pastiche in light of the Pelham II referral and AG Opinion - Papadaki, Emmanouela (Stockholm Intellectual Property Law Review, 2025)
Remixes, fan art, fan fiction, and sampling are longstanding methods of cultural expression that now flourish in online spaces. These derivative forms of creation raise pressing questions for copyright law, particularly within the European Union’s closed catalogue of exceptions and limitations. Central among them is the little-explored pastiche exception, introduced by Article 5(3) (k) of the InfoSoc Directive, alongside parody and caricature. While the meaning of parody has been clarified by the CJEU, the contours of pastiche remain uncertain. With the implementation of the DSM Directive obliging all Member States to adopt this exception, and recent cases such as Pelham II bringing the question of interpretation before the CJEU, the scope and meaning of pastiche have gained new relevance. This article argues that pastiche should be understood as an autonomous legal concept of EU law, encompassing a broad range of transformative uses where recognizable elements of pre-existing works contribute to the creation of new and noticeably different ones. Rejecting limiting requirements such as humour, stylistic imitation, or tribute, the article proposes that pastiche can function as a flexible balancing tool between rightholders’ economic interests and users’ freedom of expression. Properly interpreted, it may offer the EU a viable alternative to fair use in safeguarding contemporary creativity.